Environmental assessment of recycling carbon fibre-reinforced composites: current challenges and future opportunities - Meiirbekov, Arshyn; Amantayeva, Akniyet; Tokbolat, Serik; Suleimen, Aidar; Sarfraz, Shoaib; Shehab, Essam (Springer, 2022)
The increasing application of carbon fiber reinforced polymer composites (CFRP) across different industries raises environmental concerns. It requires focusing on the end-of-life phase of the product/material. The environmental benefits of CFRP recycling over conventional ways of treatment are apparent. However, estimating the environmental impacts is followed up with various challenges. In this study, the aspects of environmental assessment of CFRP recycling and their respective challenges are examined. CFRP recycling methods such as mechanical treatment, pyrolysis, fluidized bed process, and solvolysis have been previously studied in the context of energy and environmental assessment under the Life-Cycle-Assessment (LCA) framework. This study focused on the identification of challenges associated with variability of applied methods used, comparability, scaling results, data, uncertainty, and resource-demanding process of LCA. Recommendations on overcoming the identified challenges are provided and discussed.